Isolating soil bacteria and their potential use in systems for wastewater treatment - Mau, Silvia (2011)
The study of microorganisms from natural environments may be useful for developing a microbial consortium used for the bioaugmentation to a water treatment system. We studied microorganisms from soil samples taken in Tropical Biological Station and Aquaculture "Rio Macho", Cartago, Costa Rica and from these strains were selected most representative morphotypes. We performed four treatments in the wastewater by inoculating a suspension of each selected morphotype and the BOD (Biochemical Oxygen Demand) was quantified after these treatments. The morphotypes of the isolates were Gram negative bacilli (52,9%), Gram positive sporulated bacilli (29,4%), filamentous bacteria (11,8%) and Gram positive non-sporulated bacilli (5,9%). After the treatments there was a reduction from 94,7% to 95,85% on the initial BOD of wastewater, in contrast with the water that was not inoculated which yielded a decrease of 91%. This preliminary study demonstrates a good potential of these strains for use in systems of wastewater treatment as inocula for bioaugmentation.